Investigation of Tannins Transformation in Sanguisorbae Radix Over Carbonizing by Stir-Frying - Gu, Wei; Wang, Hao; Su, Man; Wang, Yiwei; Xu, Fei; Hu, Qinglian; Cai, Xuyi; Song, Jinyun; Tong, Huangjin; Qian, Yuerong; Zhao, Hongyu; Chen, Jun (Frontiers in Molecular Biosciences, 2022)
Carbonizing by stir-frying (CSF) is the most common technology in botanical folk medicines to enhance the effects of convergence, hemostasis and antidiarrheal. Sanguisorbae Radix (SR), a well-known herbal medicine in China, has extensive therapeutic functions, while charred SR is known as an additional product obtained from SR after CSF. In this study, mass spectrometry was used to investigate the effect of charring on tannins transformation of SR. The findings showed that the content level of tannins in SR decreased significantly after carbonizing process, while their three categories, gallotannins, ellagitannins and procyanidins, had downward trends in general. Moreover, CSF also induced the polyphenol in SR to release relevent monomers from its origins. Significant amount of hydrolysable tannins were detected by mass spectrometry, including gallotannins and ellagitannins, suggesting that hydrolysis during CSF yielded gallic and ellagic acid and their derivatives, in addition to sugar moieties. Subsequently, gallic, ellagic acid can further polymerize to form sanguisorbic acid dilactone. The amount of proanthocyanidins, the oligomers of catechin, including procyanidin, procyanidin C2, procyanidin B3 and 3-O-galloylprocyanidin B3, decreased to form catechin and its derivatives, which may further degrade to protocatechualdehyde. Quantitative analysis illustrated that the amount of gallic, pyrogallic, ellagic acid and methyl gallate, the essential effectors in SR, significantly increased after CSF, with increased ratios of 1.36, 4.28, 10.33 and 4.79, respectively. In contrast, contents of cathechin and epigallocatechin, dropped remarkably with increased ratios of 0.04 and 0.02. Tannins exhibit moderate absorption, while their relevant monomers have a higher bioavailability. Therefore, CSF is proved here to be an effective technique to the release of active monomers from the original polyphenol precursor. This study explored the mechanism by which tannins are transformed upon CSF of SR.